Road traffic noise assessment in a hospital area in Umuarama - Brazil - Moreira, Samantha Junqueira; Fonseca-Zang, Warde Antonieta Da; Bolina, Cecília de Castro; Rocha, Stella Alonso; Zannin, Paulo Henrique Trombetta (Revista Nacional de Gerenciamento de Cidades, 2021)
In hospital environments, high noise levels can result in damage to patients’ treatments, delaying their rest and recovery. The sound pressure level (SPL) in hospital areas during the day must not exceed 50 dB and 45 dB (A) at night, according to NBR 10.151/2019. This research aimed to carry out environmental monitoring of equivalent sound pressure levels (LAeq) at fifteen points in the vicinity of three hospitals in the central region of the municipality of Umuarama-PR, during working days, at four different times, in the months of August, September and November 2018 and continued in March 2019. To this end, we sought to map the LAeq of the points, compare them with data from municipal and federal legislation and relate the LAeq to the volume of vehicular traffic. The collected SPL were higher than recommended by NBR 10.151 at all times and measurement points, during the week, and when considering the municipal regulations, only one point is in the equipment’s accuracy limit. From the statistical analysis, a very strong correlation was observed between LAeq and the total volume of vehicles, and also a strong correlation between the descriptors L10 and L50 and the volume of vehicles. The Traffic Noise Index (TNI) was also calculated and the LAeq values ​​were compared with a subjective noise rating. The results show a scenario of noise pollution in the area and there is a need for the application of mitigating measures.